PENATAAN KOTA DAN MASYARAKAT PERKOTAAN: MAKASSAR SEBAGAI IBUKOTA NEGARA INDONESIA TIMUR (NIT) 1946-1950 - Ilham Daeng Makkelo (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
The main focus of this article was dynamics and transformation of Makassar when it became the capital of the State of East Indonesia (NIT), 1946-1950. The discussion is emphasized mainly on two main issues namely the arrangement of cities and community life. The first issue relates to the burden of providing infrastructure to support the role of the nation's capital. The development of facilities and infrastructure is a necessity that must be provided for smooth government at the central level. From this city, the NIT government apparatus, such as the President, ministry, and parliament, have offices and organize their activities. The second issue relates to the consequences of the arrival of people from outside Makassar to work in various institutions or organizations. Makassar is synonymous with a diverse population, concerning ethnicity, religion and profession. This working paper is more detail explain about infrastructure both in terms of administration and physical development of the city, as well as the dynamics of urban community life, especially in cultural activities. In the context of progress, they become the space of expression of modernity as the times change. The described reality explains that many different responses are occurring in each region of Indonesia in responding to the changing times. Especially in this period is better known as the revolution.